Digital Intervention Services to Promote HIV Self-Testing and Linkage to Care Services: A Bibliometric and Content Analysis-Global Trends and Future Directions - Frank Mhando; Frank Mhando; Marwa Nyankomo; Christa Hall; Kelia Olughu; Mbuzeleni Hlongwa; Mbuzeleni Hlongwa; Samuel Janson; Love O. Idahosa; Genae Hatcher; Donaldson F. Conserve; Donaldson F. Conserve (Frontiers Media S.A., 2024)
Objective: The global burden of HIV remains a critical public health challenge, particularly in sub-Saharan Africa, home to over two-thirds of individuals living with HIV. HIV self-testing (HIVST) has emerged as a promising strategy endorsed by the World Health Organization to achieve UNAIDS targets. Despite its potential, challenges persist in linking self-testers to care post a positive result. Digital health interventions, including chatbots and mobile applications, offer innovative solutions to address this gap. However, a comprehensive bibliometric analysis of the collaboration and growth in the literature at the intersection of HIVST and digital interventions is lacking.Methods: The study employs a bibliometric approach, leveraging data from the Web of Science, to analyze the characteristics, citation pattern and content of 289 articles spanning 1992-2023. The analysis involves performance assessment, scientific collaboration analysis, science mapping, and content analysis. Key bibliometric indicators, such as annual growth rate, citation impact, and authorship patterns, are explored. Collaboration patterns among countries, institutions, and authors are elucidated, and thematic mapping provides insight into the key research themes.Results: The analysis reveals a dynamic and expanding field, with an annual scientific growth rate of 12.25%. Notable contributions come from diverse sources, including North America, Europe, and Africa. High-impact journals such as JMIR mHealth and uHealth play a crucial role in disseminating research findings. African authors, including Lebelonyane R, Ford N, and Lockman S, feature prominently, reflecting a positive trend in diverse authorship. Co-citation analysis highlights influential manuscripts, with systematic reviews dominating the top-cited articles. Collaboration analysis underscores strategic partnerships globally, particularly involving the United States, Australia, South Africa, and the United Kingdom.Conclusion: This bibliometrics analysis provides a comprehensive overview of the digital health landscape in HIVST and linkage to care. It identifies key contributors, high-impact journals, and collaborative networks. The thematic map reveals nuanced research domains, including alcohol dependence, men's health, outcomes, and user acceptance. The findings offer insights for researchers, policymakers, and practitioners, guiding future directions in the evolving intersection of HIVST and digital health interventions.